2016
DOI: 10.1186/s12944-016-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum levels of proprotein convertase subtilisin/kexin type 9 (PCSK9) and atherogenic lipoproteins in patients with coronary artery disease

Abstract: BackgroundProprotein convertase subtilisin/kexin type 9 (PCSK9) is a key regulator of serum low-density lipoprotein (LDL) cholesterol levels. Recently, PCSK9 has additionally been related to metabolic risk factors such as the levels of triglycerides, apolipoprotein B (apoB), insulin, and glucose, as well as body mass index. The purpose of this study was to investigate correlations between serum levels of PCSK9 and apoB-containing atherogenic lipoproteins in patients with coronary artery disease (CAD).MethodsSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
4
18
1
Order By: Relevance
“…Lakoski et al also reported that changes in plasma PCSK9 level did not correlate with the magnitude of the LDL-C lowering response achieved with 10 mg of simvastatin 21 ) . Consistent with these reports, we previously showed that the percentage change in PCSK9 level did not correlate with the LDL-C reduction observed after statins therapy 48 ) . Furthermore, although the reduction in LDL-C was greater with pitavastatin than with pravastatin, the level of increase in PCSK9 did not differ between these statins 48 ) .…”
Section: Lipid-modifying Pharmacological Agents and Pcsk9 Concentratisupporting
confidence: 80%
“…Lakoski et al also reported that changes in plasma PCSK9 level did not correlate with the magnitude of the LDL-C lowering response achieved with 10 mg of simvastatin 21 ) . Consistent with these reports, we previously showed that the percentage change in PCSK9 level did not correlate with the LDL-C reduction observed after statins therapy 48 ) . Furthermore, although the reduction in LDL-C was greater with pitavastatin than with pravastatin, the level of increase in PCSK9 did not differ between these statins 48 ) .…”
Section: Lipid-modifying Pharmacological Agents and Pcsk9 Concentratisupporting
confidence: 80%
“…This association remained significant in a multivariate analysis (Table 3). Available literature data indicate that plasma sdLDL particles are positively related to the levels of PCSK9, at least in patients with CVD [9,10]. The observed reciprocal association between PCSK9 and sdLDL in our study could be assigned to the effects of insulin administration, since insulin increases PCSK9, but lowers sdLDL [27].…”
Section: Discussionsupporting
confidence: 58%
“…So far, a link between PCSK9 and sdLDL particles has been scarcely investigated. A positive correlation was reported in patients with CVD [9,10], whereas no association was found in healthy subjects [11,12]. Hence, it is possible that the relationship between circulating PCSK9 and sdLDL particles varies in health and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in 2003 PCSK9 has emerged as a significant modulator of LDL metabolism [10, 11]. Loss of function mutations of PCSK9 are associated with low plasma LDL-C levels [12, 13].…”
Section: Introductionmentioning
confidence: 99%